The pathway for the conversion of dihydroagnosterol into cholesterol in rat liver. - Tavares, I A (1977)
Dihydroagnosterol is demethylated by a rat liver homogenate to give 4,4'-dimethylcholesta 7,9-dienol and then cholesta-7,9-dienol. The cholesta-7,9-dienol is isomerized to cholesta-8,14-dienol, which is converted into cholesterol by the normal pathway.